Opportunities and Challenges for Implementing Guidance and Counseling in Junior High Schools in Technological Development - Mutia Hafizah; Firman; Neviyarni S (Manajia: Journal of Education and Management, 2024)
The implementation of guidance and counseling (GC) in junior high schools (SMP) has undergone significant changes with the advancement of technology. This article discusses the opportunities and challenges in modern GC, including the accessibility of services through digital platforms, the personalization of data-based programs, and the development of digital literacy for students and teachers. The challenges faced include the need for adequate technological infrastructure, the digital divide among students, and data privacy risks. This study uses a case study method in several junior high schools in Indonesia. The results show that technology can enhance the effectiveness of GC but requires policy support and continuous training. This article provides recommendations for optimizing technology-based GC in junior high schools.